Contribution of Ruminal Fungi, Archaea, Protozoa, and Bacteria to the Methane Suppression Caused by Oilseed Supplemented Diets - Wang, Shaopu; Giller, Katrin; Kreuzer, Michael; Ulbrich, Susanne E.; Braun, Ueli; Schwarm, Angela (Frontiers in Microbiology, 2017)
Dietary lipids can suppress methane emission from ruminants, but effects are variable. Especially the role of bacteria, archaea, fungi and protozoa in mediating the lipid effects is unclear. In the present in vitro study, archaea, fungi and protozoa were selectively inhibited by specific agents. This was fully or almost fully successful for fungi and protozoa as well as archaeal activity as determined by the methyl-coenzyme M reductase alpha subunit gene. Five different microbial treatments were generated: rumen fluid being intact (I), without archaea (‒A), without fungi (‒F), without protozoa (‒P) and with bacteria only (‒AFP). A forage-based diet given alone or supplemented with crushed full-fat oilseeds of either safflower (Carthamus tinctorius) or poppy (Papaver somniferum) or camelina (Camelina sativa) at 70 g oil kg‒1 diet dry matter was incubated. This added up to 20 treatments with six incubation runs per treatment. All oilseeds suppressed methane emission compared to the non-supplemented control. Compared to the non-supplemented control, ‒F decreased organic matter (OM) degradation, and short-chain fatty acid concentration was greater with camelina and safflower seeds. Methane suppression per OM digested in ‒F was greater with camelina seeds (-12% vs. -7% with I, P = 0.06), but smaller with poppy seeds (-4% vs -8% with I, P = 0.03), and not affected with safflower seeds. With ‒P, camelina seeds decreased the acetate-to-propionate ratio and enhanced the methane suppression per gram dry matter (18% vs. 10% with I, P = 0.08). Hydrogen recovery was improved with ‒P in any oilseeds compared to non-supplemented control. No methane emission was detected with the ‒A and ‒AFP treatments. In conclusion, concerning methanogenesis, camelina seeds seem to exert effects only on archaea and bacteria. By contrast, with safflower and poppy seeds methane was obviously reduced mainly through the interaction with protozoa or archaea associated with protozoa. This demonstrated that the microbial groups differ in their contribution to the methane suppressing effect dependent on the source of lipid. These findings help to understand how lipid supplementation and microbial groups interact, and thus may assist in making this methane mitigation tool more efficient, but await confirmation in vivo.